The influence of the need-for-touch on the online purchase propensity : a comparative study between Portugal and China - Silva, Jorge Miguel Ribeiro Moreira da (2015)
This master thesis examines the influence of the Need-For-Touch (NFT) on the online purchase propensity through a comparative study between Portuguese and Chinese consumers. Although, NFT has been a major topic of research over the past years, the link between the consumer NFT and the individual national background has rarely been empirically proven. The same occurs for the impact of the consumer NFT on the online purchase propensity and for the possible mediating variables between these constructs. In order to further research these topics, a study was performed using multivariate analyses of variance and structural equation modelling to validate the proposed model. The research revealed that the consumer NFT does not influence directly the online purchase propensity. Instead, this relationship is mediated by other variables such as brand experience and online research propensity. The results showed that a consumer with a high NFT level is more likely to have a stronger brand experience. Additionally, it was noticeably proved that the perceived credibility of the information and the brand experience impact positively the perceived product quality which, in turn, impacts the propensity to research online and, consequently, the online purchase propensity. Chinese consumers revealed higher NFT levels than Portuguese consumers while the former displayed similar instrumental and autotelic NFT levels and the latter revealed substantial differences between both. According to this study, the consumers’ nationality seems to affect the relevance of touch for different products. This study provides useful information regarding the impact of the consumers’ NFT on the online purchase propensity and uncovers interesting differences between the NFT level of Portuguese and Chinese consumers.